Multi-level climate change planning: An analysis of the Italian case. (1st July 2021) - Pietrapertosa, Filomena; Salvia, Monica; De Gregorio Hurtado, Sonia; Geneletti, Davide; D'Alonzo, Valentina; Reckien, Diana
Abstract: As recognized by the Paris Climate Agreement of the United Nations Framework Convention on Climate Change (UNFCCC), local and subnational regions are crucial actors to achieve international mitigation and adaptation commitments. Scientific literature and empirical evidence point at multi-level climate governance as a crucial factor to engage subnational levels in the achievement of national and international objectives. This work focuses on the multi-level climate governance arrangements in Italy to investigate how Italian regions/provinces/cities are contributing to the achievement of national commitments. To this purpose, the paper undertakes a review of the climate policies of different tiers of government adopted to date and of the interrelationships among them. The results of the analysis show that the effective coordination between the different government levels should be strengthened to further incentivize and support initiatives at the local level. Results also show the relevant role played by international regional and city climate networks in boosting local and regional climate planning in Italy. Highlights: Climate plans of 21 Italian regions, 32 provinces, and 32 cities were assessed. 57% of the Italian regions; 13% of provinces and 78% of cities set a carbon target. 10% of regions, no province, and 2% of municipalities have an adaptation plan. Cities are more active than provinces and regions in defining mitigation policies. Active multilevel governance is effective for implementing climate plans in cities.